On equilibrium states of superfluid with d-wave pairing - Ivashin, A.P.; Kovalevsky, M.Y.; Chekanova, N.N. (Вопросы атомной науки и техники, 2002)
The equilibrium states of quantum fluid with d-pairing classification is carried out on the basis of the quasiaverages concept. It is shown, that the set of such an equilibrium states can be classified in the terms of the orbital momentum quantum number, relevant to the projection of the orbital momentum of the superconducting electron pair on an anisotropy direction. The explicit expression of three admissible unbroken symmetry generators and relevant order parameter equilibrium values are found.